Effects of starters with different NDF/starch ratio on rumen fermentation parameters and rumen microorganisms in lambs - Zhao, Haibi; Lv, Feng; Liu, Guohua; Pang, Xin; Han, Xiaoxia; Wang, Xiaojuan (Frontiers in Veterinary Science, 2023)
The purpose of this study was to explore the effects of different NDF/starch ratio starters on rumen fermentation parameters and rumen development in lambs and to predict the function of rumen microorganisms by using metagenomic technology. In this study, 12 lambs with birth weight of (3.0±0.5) kg were selected Lambs of Hu sheep were randomly divided into two groups, feeding starter with NDF/starch ratio of 0.5 (group A) and 1.0 (group C), respectively. Animals were fed with milk replacer from 10 days of age to 35 days of age, and the whole experiment was free to eat starter and drink water. Slaughtered at 56 days of age, samples were collected and determined. The results are as follows: (1) Acetic acid, microbial protein (MCP), rumen weight, papilla width and base thickness in group A were significantly higher than those in group C (P< 0.05); (2) Illumina sequencing platform was used to obtain a total of 151,601.2Mbp of data from 12 rumen contents, with an average of 12,633.43Mbp, and the quality control efficiency reached 99.729%. Among the genes that could be annotated into the NR database, the proportion of annotated to the genus and species level of phylum were 90.07% 86.29% 82.88% 82.40% 74.59% 69.91% and 47.75, respectively. (3) We used functional annotation, functional abundance analysis, functional differential analysis and metabolic pathway analysis to explore the function of the rumen microflora of lambs. Annotated results based on the KEGG database showed that metabolism had the highest gene abundance, followed by genetic information processing, cellular processes and environmental information processing. The annotation results based on CAZy database showed that glycoside hydrolase (GHs) gene was the most abundant, followed by glycosyltransferase (GTs). In conclusion, NDF/ starch 0.5 starter had better effect.